Fungsi Kepolisian Dalam Penanggulangan Kejahatan Seksual Yang Dilakukan Oleh Anak (Studi Kasus Di Polrestabes Makassar) - Rosi, Eka Eman; Yasmin, Muhammad; Jufri, Supriadi; Cahyani, Afrilia; Fitria, Ika; Rifky, Muh. (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim to be achieved in this research is to find out and analyze the factors that cause sexual crimes committed by children. And to find out and analyze what obstacles the police have in preventing sexual crimes committed by children. The type of data used to obtain data to compile this research is primary data, namely data obtained from field objects (field research), namely research carried out by taking data from agencies authorized to write and supported by secondary data, namely data obtained from materials. -material, namely library research, namely by reading books that are related to the object in question in accordance with this research, then comparing them with each other and from the results of the comparison, conclusions are drawn as study material. Factors that hinder the handling of sexual crimes committed by children come from several factors, namely legal factors, law enforcement, society, facilities and culture. Which is where factors originating from community factors have the most influence in overcoming sexual crimes committed by children because legal awareness in society is still lacking.